Quality Control of Midsole Products Using Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA) Methods in PT. XYZ - Rossadi, Paradika; Sumiati, Sumiati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT. XYZ is a company engaged in the shoes industry. One such product is Midsole. In the Midsole production process, defects such as burning defects, tearing defects, bubble defects and dirty defects that affect quality are still found. The purpose of this study was to determine the proportion of defects that most often occur and the factors that cause defects and to provide suggestions for improving the quality of Midsole. The methods used are Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA). The SQC tools include check sheets, statistics, histograms, pareto charts, scatter diagrams, control charts, and fishbone diagrams. Then continue the FMEA analysis for suggestions for corrective action. Based on the results of research on Statistical Quality Control (SQC) it is known that the most dominant defects in midsole are burning (38%), then dirty (24,4%), bubble (20%), and tearing (17,6%) ). Based on the results of research on Failure Mode Effect Analysis (FMEA) it is known that the highest cause of problems with RPN 343 is Mold Release Agent spraying is uneven. Suggestions for improvement that can be proposed namely. Conduct training for workers on how to spray MRA according to stamdart and  determine the rest time limit so that the injection engine does not overheat.